The Impact of Social Influence, Product Knowledge, and Fear of Missing Out (FOMO) towards Purchase Intention on Alcoholic Beverage in Bali - Ida Bagus Nyoman Dwisuardinata; Gede Sri Darma (Bina Nusantara University, 2023)
Based on the enactment of official government regulations in Governor Regulation No. 1 of 2020 concerning the Governance of Balinese Fermented and Distilled Drinks, arak Bali has started to appear publicly. It brings many advantages for the Balinese, especially in the business of fermented drink production. However, it is still unknown about consumer behavior regarding the interest in arak Bali, especially among Balinese people who live socially. The research aimed to determine the effect of social influence, product knowledge, and Fear of Missing Out (FOMO) on purchase intention in arak Bali. The population used was millennials and Generation Z in Denpasar City who had looked for information and consumed arak Bali. The amount of sample used was 153 respondents. Then, data analysis model Â used Â the Structural Equation Model (SEM) with AMOS 24. Based on the results of data processing with AMOS 24, it can be concluded that there is a significant and positive effect of social influence on purchase intention, product knowledge on purchase intention, social influence on FOMO, and product knowledge on FOMO. Meanwhile, FOMO has no significant but positive effect on purchase intention. It is known that the effect of product knowledge on purchase intention has the greatest influence and value in the research.